Directors' duties: improper purposes or implied terms?. (1st July 2013) - Lim, Ernest
<x xml:space="preserve">Abstract</x> This paper challenges the prevailing assumption that the directors' duty to act for proper purposes under s 171 (b) of the Companies Act 2006 is well‐grounded on authorities such as Howard Smith Ltd v Ampol Petroleum Ltd, Hogg v Cramphorn Ltd, Lee Panavision Ltd v Lee Lighting Ltd and Extrasure Travel Insurances Ltd v Scattergood. It advances the argument that a close analysis of these authorities shows that, despite the use of the language of proper purpose, the primary and central justification for impugning the director's exercise of powers in question is that an implied term of the company's constitution was contravened. Given that case‐law support for the proper purpose duty is at best overstated and at worst misconceived, a consideration of whether future cases concerning whether directors have breached their duties should be decided on the basis of whether an implied term of the constitution has been contravened under s 171(a), instead of whether directors have exercised their powers for proper purposes under s 171(b), is warranted. It is submitted that deciding cases based on implied terms under s 171(a) is more defensible because: (i) high authorities such as Attorney General of Belize v Belize Telecom and Equitable Life Assurance Society v Hyman endorse the use of implied terms as a technique for controlling the exercise of discretionary powers conferred on directors; (ii) a principled approach for implying terms can be derived from these authorities; (iii) there are safeguards that are built into the doctrine of implied terms; (iv) the application of the improper purpose doctrine gives rise to perennial problems; and (v) that doctrine is based on a fallacious conceptual justification.